The epidemiological landscape of lung cancer: current status, temporal trend and future projections based on the latest estimates from GLOBOCAN 2022 - Yuting Ji; Yunmeng Zhang; Siwen Liu; Jingjing Li; Qianyun Jin; Jie Wu; Hongyuan Duan; Xiaomin Liu; Lei Yang; Yubei Huang (Journal of the National Cancer Center)
Background: Given the relatively unfavorable prognosis and significant geographic differences in lung cancer burden, it is critical to update the global landscape of lung cancer to inform local strategies. Methods: Based on the GLOBOCAN 2022, the age-standardized incidence rate (ASIR) and mortality rate (ASMR) were compared and linked to the Human Development Index (HDI) across different populations. The temporal trends in ASIR/ASMR were characterized as estimated annual percentage change (EAPC), and demographic projections were performed up to 2050. Results: Globally, an estimated 2,480,675 cases and 1,817,469 deaths from lung cancer occurred in 2022. Both ASIR and ASMR of lung cancer varied widely by world region, with ASIR ranging from 2.06 to 39.38 per 100,000 and ASMR from 1.95 to 31.70 per 100,000. China alone accounted for >40 % of cases and deaths worldwide. Both ASIR and ARMR of lung cancer increased with HDI (R2: 0.54 and 0.47, all P values <0.001), regardless of gender. Based on available data, both ASIR during 2001–2010 and ASMR during 2001–2015 showed decreasing trends in males (EAPC: 1.50 % and −2.22 %) but increasing trends in females (EAPC: 1.08 % and 0.07 %). Similar trends in ASIR and ASMR were observed among the elder population (≥50 years); however, downward trends were observed in the younger population (<50 years). Alongside the aging and growth of the population, estimated cases and deaths from overall lung cancer would increase by 86.2 % and 95.2 % up to 2050 as compared with estimates in 2022, respectively. Notably, increased early-onset lung cancer was only observed in transitioning countries, while decreased early-onset lung cancer was observed in transitioned countries. Conclusion: Lung cancer maintained as the leading cancer burden worldwide. Unless timely preventive interventions in tobacco mitigation, early screening, and precise treatment, the global lung cancer burden is expected to increase in the future, especially for transitioning countries.